From Insect Pheromones to Mating Disruption Theory and Practice - Lucchi, Andrea; Benelli, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book, a reprint of the successful Insects Special Issue "From Insect Pheromones to Mating Disruption: Theory and Practice", includes laboratory and field studies dealing with insect pheromones, as well as on mating disruption efficacy against insect species of economic importance, with special reference to the development and optimization of mating disruption approaches, their mechanisms of action, and possible non-target effects.